2022
DOI: 10.3390/ijerph191912360
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Social Factors Associated with Intimacy Needs in Divorced and Widowed Older Chinese Women

Abstract: The rapidly ageing population, the growing rate of divorce, and the longer life expectancy of women compared with men have resulted in a large proportion of older Chinese women being alone. The sexual health and intimacy needs of this group of women are ignored due to traditional Chinese cultural values that undermine older adults’ needs for sex and intimacy, and the subordinate position of women in society. The present study used a quantitative survey method to investigate bio-psycho-social factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…In term of marriage status, being divorced or widowed was signi cant contributor to SHS and stress. This evidenced the ndings that poor marital status was statistically associated with psychological distress and poor health status [55]. With regard to the BMI classi cations, our study also showed that the risk of SHS and stress among normal participants is lower than that among thin participants.…”
Section: Covariate Analysissupporting
confidence: 75%
“…In term of marriage status, being divorced or widowed was signi cant contributor to SHS and stress. This evidenced the ndings that poor marital status was statistically associated with psychological distress and poor health status [55]. With regard to the BMI classi cations, our study also showed that the risk of SHS and stress among normal participants is lower than that among thin participants.…”
Section: Covariate Analysissupporting
confidence: 75%
“…Additionally, coping with a life-threatening illness and accepting ostomy surgery can lead to emotional and psychological problems (Ayaz Alkaya, 2019 ; Davidson, 2016 ). Such as anxiety, depression (Knowles et al, 2013 ), fear of recurrence (Custers et al, 2016 ), low self-esteem relevant to poor body image (Jayarajah & Samarasekera, 2017 ), stigma (Yuan et al, 2018 ), social isolation (Ji & Yan, 2022 ), or post-traumatic stress disorder (Shin & Choi, 2021 ). These problems can impact patients’ ability to engage in intimate relationships.…”
Section: Introductionmentioning
confidence: 99%